Solution for heat conduction in a solid with temperature dependent thermal conductivity - Png, Wei Quan (2017)
Heat transfer is the exchange of heat energy between two bodies. There are three different modes of heat transfer, namely conduction, convection and radiation. In this project, the author will be focusing on how heat transfer by conduction can be affected by a change in thermal conductivity. Heat conduction is the movement of heat flowing from a solid to another internally through process of the collision of particles and having a temperature difference between the particles. This heat conduction equation will be in the form of a nonlinear partial differential equation when there is a temperature dependence thermal conductivity. By means of the Fourier series and MATLAB, the author will then come out with the temperature contour line of a solid with different thermal conductivities. Comparisons will then be made among the results obtain to find out how heat conduction will vary with different thermal conductivity. The author will also discuss the importance of thermal conductivity and how applicable it will be to our real world and how it has been part of our daily life. This report will then be concluded with what the author has learned from taking on this research.